Evaluation of the Effects of Nanoparticles in the Treatment of Diabetes Mellitus: A Systematic Review and Meta-analysis - Fatemeh Rabiee; Neda Mehralizadeh; Samira Jalalinezhad; Zahra Ebrahimi; Somaye Jamali (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
Background and aim: Due to the importance of the issue in the treatment and prevention of diabetes mellitus, in the present study, it is decided to investigate the role of nanoparticles in the treatment or prevention of the development of diabetes mellitus. The aim of the present study was to evaluate the effects of nanoparticles in the treatment of diabetes mellitus.Material and methods: The present study is a systematic review and meta-analysis based on PRISMA 2020 Checklist. Databases of PubMed, Scopus, Web of Science, EBSCO, ISI Web of knowledge, and Embase were searched for systematic literature until 20 November 2022. A 95% confidence interval for mean differences with the random effect model and REML method were calculated. Meta-analysis was performed using Stata/MP v.17 software.Results: In the initial review, duplicate studies were eliminated, abstracts of 219 studies were reviewed, and two authors reviewed the full text of 184 studies. Finally, nine studies were selected. The mean differences in Fasting blood sugar between the silver nanoparticles group and zinc oxide nanoparticles vs. group was -209.92 (MD: -209.92 95% CI; -272.56, -147.28; p=0.00) and -1.58 (MD: -1.58 95% CI; -2.38, -0.78; p=0.00), respectively.Conclusions: Based on the present meta-analysis, administering silver nanoparticles and zinc oxide nanoparticles in animal models can have antidiabetic effects and reduce fasting blood sugar levels.